2023
DOI: 10.1007/s41685-023-00276-9
|View full text |Cite
|
Sign up to set email alerts
|

North–South discrepancy and gender role attitudes: evidence from Vietnam

Abstract: In Vietnam, it is commonly believed that gender norms, sex labour segregation, and structural organization of social institutions often favour male dominance while restricting women’s roles in domestic spheres. However, there is a scant literature of Vietnamese scholarship on the determinants of gender role attitudes, especially geographical disparities. This paper aims to fill this void by using a nationally representative survey with 8288 respondents. Our findings suggested that age, marital status, religion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Our findings from this empirical analysis align with those reported in previous studies on the role of Confucianism on gender inequality in Vietnam [ [55] , [56] , [57] , [58] ]. Among these studies [ 55 ], concluded that Confucianism negatively affects gender inequality in labour, health, and educational outcomes.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings from this empirical analysis align with those reported in previous studies on the role of Confucianism on gender inequality in Vietnam [ [55] , [56] , [57] , [58] ]. Among these studies [ 55 ], concluded that Confucianism negatively affects gender inequality in labour, health, and educational outcomes.…”
Section: Resultssupporting
confidence: 90%
“…Among these studies [ 55 ], concluded that Confucianism negatively affects gender inequality in labour, health, and educational outcomes. However, their findings also indicate that when females pursue more years of schooling, they perform better than males [ 56 ]. examined gender role attitudes in Vietnam using a sample of 8288 respondents.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, for women, items measure DSI and the opportunity to interact with the dominant society outside the home. Prior research shows a traditional division of gender roles in Vietnamese families in Vietnam, as well as in Vietnamese migrant families, where women, in general, are responsible for most domestic activities and care-related work ( Do et al, 2023 ; Knodel et al, 2005 ; Nghe et al, 2003 ; Nguyen et al, 2021 ). Thus, it seems plausible that, while both genders stay equally embedded into their ethnic society, women might have fewer opportunities to immerse into the dominant society because they are busy with domestic activities and care work (in our sample, 64% of men were working, compared to only 47% of women).…”
Section: Discussionmentioning
confidence: 99%